Islamist politics in migrant cities: local identity cleavages and intra-party politics in Turkey. Issue 4 (1st October 2016) - Ocaklı, Feryaz
Abstract: This article explores how the local party organizations of the Adalet ve Kalkinma Partisi (Justice and Development Party—AKP) interact with complex social structures in migrant-receiving cities in Turkey. Islamist movements are widely viewed as uniquely capable of appealing to working-class migrants. However, the support for Islamist parties varies across migrant-receiving cities. This article argues that local party organizations face two potential sources of discord that they have to resolve in order to build support in migrant neighbourhoods. They have to bridge the regional identity cleavages among different migrant communities while surmounting intra-party conflicts. In pursuing this argument, this article opens up the black box of local identity politics in the industrial heartland of Turkey and provides an ethnographic account of intra-party conflicts and political survival within the AKP.